SPIRIT AT WORK, SUSTAINABLE LEADERSHIP AND ORGANIZATIONAL COMMITMENT: THE PERSPECTIVE OF ACCOUNTING STAFF - Erna; Chen, Robin; Murtanto; Arsjah, Regina Jansen (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study aims to prove and analyze the influence of sustainable leadership and spirit at work on employee commitment to the company. The private companies used are in Indonesian e-commerce, health, manufacturing, and education sectors. The employees intended work as an internal accountant. Furthermore, this study utilizes the convenience sampling technique to sample them, and can acquire 152 people based on the survey between May and June 2024. Therefore, their response is analyzed using a structural equation model based on partial least squares. After testing these two relationships, this study declares a positive association between sustainable leadership and employee commitment. Additionally, the spirit at work is positively related to employee commitment to the company. Based on this evidence, leaders can apply a sustainable leadership style and build a working atmosphere that leads to spirit at work and motivates employees to commit to their work.